Evaluasi Waktu Tunggu Pelayanan Resep Pasien BPJS Kesehatan Rawat Jalan Di Rumah Sakit Umum Bella Bekasi - Budi Setyorini; Dety Mulyanti (Jurnal Riset dan Inovasi Manajemen, 2023)
The Pharmacy Installation Section of the BPJS Outpatient Unit is that there are still many patients who complain about the waiting time for drug services. Calculating the waiting time for prescription drug service and concoction medicine, then analyzing compliance with the minimum service standard for the long waiting time category. Evaluating performance in providing health services to BPJS Outpatient patients and can help improve the quality and efficiency of health services. Quantitative and qualitative methods in analyzing the data obtained. Quantitative methods can be used to calculate average waiting times and other statistical analyses, while qualitative methods can be used to analyze interview data and gain a deeper understanding of the factors that affect waiting times. Average waiting time needed to complete a concoction recipe is 49 minutes and to complete a non concoction recipe 32 minutes. The number of standard non-concoction recipes is 699 recipes. Meanwhile, there were 2 recipes that did not meet the standards. For concoction recipes, 146 recipes have met the standard. The waiting time for prescription service at the pharmacy installation for outpatients at BPJS Bella General Hospital for non-concoction recipes still does not meet the standards, while for concoction recipes they meet the minimum standards.